PENGEMBANGAN LKPD IPA MODIFIED FREE INQUIRY UNTUK MENUMBUHKAN KESADARAN PEDULI LINGKUNGAN AKIBAT PENAMBANGAN PASIR DI KAWASAN KECAMATAN MUNTILAN, KABUPATEN MAGELANG DEVELOPMENT OF SCIENCE STUDENT WORKSHEETS MODIFIED FREE INQUIRY TO RAISE AWARENESS OF THE CONCERNED FOR THE ENVIRONTMENT AS A RESULT OF SAND MINING IN MUNTILAN SUB-DISTRICT, MAGELANG DISTRICT - Agustina Martha Eristya; Dadan Rosana; Purwanti Widhy Hastuti (Jurnal TPACK IPA, 2017)
Penelitian ini bertujuan untuk mengetahui kelayakan LKPD IPA, respon peserta didik dan keefektifan LKPD IPA Modified Free Inquiry yang dikembangkan untuk menumbuhkan kesadaran peduli lingkungan akibat penambangan pasir di kawasan Kecamatan Muntilan, Kabupaten Magelang. Penelitian ini merupakan penelitian Research and Development (RD). Instrumen yang digunakan berupa angket penilaian LKPD IPA, angket respon peserta didik terhadap LKPD IPA, angket sikap peduli lingkungan, dan lembar observasi sikap peduli lingkungan. Subjek penelitian melibatkan 2 dosen ahli dan 2 guru IPA sebagai validator, serta 24 peserta didik kelas VII C SMP Negeri 1 Muntilan. Teknik analisis data menggunakan analisis deskriptif validasi dan respon peserta didik terhadap LKPD IPA, gain score sikap peduli lingkungan dan one t-test, serta presentase sikap peduli lingkungan. Hasil penelitian ini adalah kelayakan LKPD IPA memperoleh nilai A (sangat baik). Respon peserta didik terhadap LKPD memperoleh nilai A (sangat baik). LKPD IPA dapat menumbuhkan sikap peduli lingkungan dibuktikan dengan hasil perhitungan dengan gain score dan melalui uji t. Presentase dari sikap peduli lingkungan berdasarkan observasi pada setiap pertemuan mengalami kenaikan.Kata kunci: LKPD IPA, modified free inquiry, sikap peduli lingkunganThe aim of this research are to know the feasibility and the response of the learners and determine effectiveness of science student worksheet Modified Free Inquiry developed to raise the environmental awareness attitudes as a result of sand mining in Muntilan Sub-district, Magelang District.Type of this research is Research and Development (RD). The instruments are questionnaire for evaluation science student worksheet, questionnaires of response learners to the science student worksheet, questionnaires the environmental awareness attitudes and form of observation for the environmental awareness attitudes. Subject of this research involving 2 experts and 2 science teachers as the validator and 24 learners class VII C of Muntilan 1 Junior High School. The data were analized using descriptive analysis for validation and the response of the learners to the science student worksheet, gains score the environmental awareness attitudes and t-test type one-t test, and the precentage of the environmental awareness attitudes. The results of this research are the feasibility of science student worksheet obtain the value A (excellent). The response learners obtain the value A (excellent). Science student worksheet can raise the environmental awareness attitudes by the results of the calculation with the gains score and the significant of t-test. Precentage of the environmental awareness attitudes based on observation increase on every meeting.Keywords: Science student worksheet, modified free inquiry, the environmental awareness attitudes